2002
DOI: 10.3354/dao049051
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the distribution of Myxobolus cerebralis, the causative agent of whirling disease, in the Cache la Poudre River, Colorado

Abstract: Oligochaetes, triactinomyxons (TAMs), and age-0 trout were sampled in the upper Cache la Poudre River, Colorado, to determine the distribution of Myxobolus cerebralis during 1997 and 1998. Densities of the intermediate host, the oligochaete Tubifex tubifex, were 3.5 orders of magnitude higher in the M. cerebralis-infected Poudre Rearing Unit (PRU) trout rearing ponds than at any of the river sampling reaches. Oligochaetes, including T. tubifex, were rare in the river (1 oligochaete m -2 ), except in a few stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 20 publications
3
30
0
5
Order By: Relevance
“…The amount of organic material in a stream is positively associated with the occurrence of several invertebrate hosts. For example, abundance of T. tubifex is correlated with high organic material (Allen and Bergersen 2002;Kaeser et al 2006). Similarly, greater abundances of bryozoans occur in rivers with higher nutrient levels (Hartikainen et al 2009) and increased growth and higher intensity of infection with T. bryosalmonae in bryozoans at higher nutrient/food levels (Hartikainen and Okamura 2012).…”
Section: Nutrient Effectsmentioning
confidence: 99%
“…The amount of organic material in a stream is positively associated with the occurrence of several invertebrate hosts. For example, abundance of T. tubifex is correlated with high organic material (Allen and Bergersen 2002;Kaeser et al 2006). Similarly, greater abundances of bryozoans occur in rivers with higher nutrient levels (Hartikainen et al 2009) and increased growth and higher intensity of infection with T. bryosalmonae in bryozoans at higher nutrient/food levels (Hartikainen and Okamura 2012).…”
Section: Nutrient Effectsmentioning
confidence: 99%
“…It has been recently demonstrated that suscep tibility to M. cerebralis is variable among oligochaete strains and genotypes (Stevens et al, 2001;Beauchamp et al, 2002). Environmental factors (e.g., habitat sub strates, nutritional potentials and dissolved oxygen lev els) influencing the distribution of oligochaetes have been investigated in relation to the severity of myxozoan infections (Allen and Bergersen, 2002;Koprivnikar et al, 2002;Blazer et al, 2003;Liyanage et al, 2003). It is likely that anthropogenic activities in streams and rivers, e.g.…”
Section: Biology Of Invertebrate Hostsmentioning
confidence: 99%
“…Although T. tubifex worms have been found in abundance at organically enriched sites in the West (Allen and Bergersen 2002), the species appears to be common and widely distributed throughout stream systems that have experienced whirling disease epizootics (Zendt and Bergersen 2000). The spread of M. cerebralis across the intermountain West landscape additionally supports the notion that i?…”
Section: Introductionmentioning
confidence: 90%
“…We suspect that T. tubifx sediment habitat, such as the Cache La Poudre River in Colorado, contain these worms and have experienced whirling disease epizootics (Zendt and Bergersen 2000;Allen and Bergersen 2002). Nonetheless, the availability of fine sediment habitat has been considered a risk factor for M. cerebralis establishment in this region (Schisler and Bergersen 2002).…”
Section: Falling Springs Branchmentioning
confidence: 99%